2020
DOI: 10.21873/invivo.11979
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-cancer Activity of MH-30 in a Murine Melanoma Model Treated With Cisplatin and its Alleviated Effects Against Cisplatin-induced Toxicity in Mice

Abstract: Background/Aim: Although cisplatin is an effective anticancer drug, its toxic effects on normal tissues limit its use. We developed a herbal formula, MH-30, with increased fat-soluble polyphenols by improving the manufacturing method of HemoHIM. In this study, we examined whether the combination of MH-30 with cisplatin exerts synergistic antitumor effect while it reduces cisplatininduced toxicities. Materials and Methods: MH-30 was produced by adding the ethanol-insoluble fraction to its extract after decoctin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Compared with untreated control, Ad@NK‐treated mice showed no significant difference in body weights, major hepatorenal function index (ALT activity, AST activity, and BUN concentration), and blood routine and biochemical indexes (WBC, RBC, Hb, platelet, neutrophil, lymphocyte, monocyte, and RBC distribution width) (Figure S16a–c, Supporting Information). [ 45 ] In addition, the histological data indicated that Ad@NK treatment did not induce remarkable injury in the main organs (Figure S16d, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with untreated control, Ad@NK‐treated mice showed no significant difference in body weights, major hepatorenal function index (ALT activity, AST activity, and BUN concentration), and blood routine and biochemical indexes (WBC, RBC, Hb, platelet, neutrophil, lymphocyte, monocyte, and RBC distribution width) (Figure S16a–c, Supporting Information). [ 45 ] In addition, the histological data indicated that Ad@NK treatment did not induce remarkable injury in the main organs (Figure S16d, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The MH-30, a novel herbal formulation, demonstrated significant effects in melanoma models when combined with cisplatin. 29 The formulation, containing extracts from Angelica Radix , Cnidii Rhizoma , and Paeonia Radix enhanced the anti-cancer efficacy of cisplatin, leading to decreased tumor weight in melanoma-bearing mice. This enhancement may be attributed to increased NK cell activity and IFN-gamma secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The first group (Vehicle treated group, n=7) was orally administrated the same volume (200 µl) of 1x PBS every day for five weeks. The second group (Cis treated group, n=7) was injected intraperitoneally with Cis (4 mg/kg) every two days from day 26 to day 37, because long-term administration of Cis causes serious toxicity and can lead to death (27). The other three groups were administered a low (250 mg/kg; LoAEC treated group, n=7), medium (500 mg/kg; MiAEC treated group, n=7) or high concentration of AEC (1,000 mg/kg; HiAEC treated group, n=7) orally every day for 37 days.…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 99%